Compliance of Patients with Locally Advanced Colorectal Cancer to Chemotherapy Using FOLFOX compared to XELOX Regimen - Kusnadi, Dana S.; Putranto, Agi S.; Saunar, Rofi Y.; Kekalih, Aria; Moenadjat, Yefta (UI Scholars Hub, 2016)
Introduction. Adjuvant chemotherapy become the treatment of choice in advance colorectal cancer to prevent recurrence. Studies showed that FOLFOX and XELOX regimen has been proven to increase overall survival rate and disease free survival. This study is aimed to compare XELOX response to FOLFOX regimen in our center, which is characterized by advanced stage neoplasm in the first presentation with low compliance. It also aimed to find out affecting factors of such response. Method. We run a retrospective study enrolled of 133 subjects with colorectal carcinoma of stage III and high–risk stage II who received adjuvant chemotherapy and treated in dr. Cipto Mangunkusumo– and Fatmawati General Hospital. Consecutive sampling was instituted, CEA level and one year mortality rate was recorded as variables of the efficacy, which was then associated with subjects’ compliance. Statistical analysis was done using Chi square or Fisher test, and a multivariate logistic regression. Significance was found as the difference met <0.05 with confidence interval of 95%. Results. We found there is no significant difference between the two regimens with efficacy (p = 0.61). There is significant correlation between the regimen (p = 0.001 and 0.000); with compliance is found much higher in FOLFOX (86% compared to 45%). We also found statistically significant of influencing factors the efficacy, i.e. Karnofsky score >90 (OR = 5.8; p = 0.004), body mass index both of normal and more (OR = 4.7; p = 0.006), and with histopathologic grading of moderate differentiated (OR = 6.3; p = 0.003). Conclusion. FOLFOX and XELOX regimen has been shown to have a same efficacy in response in our center. However, compliance showed a strong correlation to efficacy and FOLFOX regimen showed much higher rather than XELOX. Karnofsky score and body mass index should be subjects of consideration to increase the response of such adjuvant chemotherapy.